NEWBORN SCREENING PROGRAM IN SLOVENIA - Jernej Kovač; Barbka Repič Lampret; Žiga Iztok Remec; Teja Sever Šraj; Urh Grošelj (The Society for Children with Metabolic Disorders, 2024)
Newborn Screening (NBS) is one of the most significant and successful public health initiatives globally. Implemented in various capacities across most developed countries, NBS programs vary in scope and focus, with the most comprehensive screening for over 50 conditions. In Slovenia, NBS is a vital component of the public health system, initiated in 1979 with screenings for phenylketonuria. The program has evolved and expanded with the introduction of new technologies such as mass spectrometry for metabolic diseases and immunoreactive and genetic tests for conditions like cystic fibrosis, spinal muscular atrophy, and primary immune deficiencies. Dried blood spots on filter paper facilitate easy transportation to the University Children's Hospital Ljubljana for the analysis. Professional sample collection by maternity ward staff ensures sample quality, which is critical for successful laboratory testing. Participation in the program is universal for all newborns, with an option for parental refusal. Hundreds of Slovenian newborns have been successfully diagnosed and treated, underscoring the program's importance. With the advent of new medicines and therapies, the scope of NBS is set to expand. The program's success relies on the synergy between participating groups - maternity hospitals, the pediatric clinic, and the laboratory.